Are There Entity-Specific Criteria for Initiation of Specialized Palliative Care for Incurable Cancer? A Scoping Review - Gahr, Susanne; Brunner, Sarah; Heckel, Maria; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2023)
Background/Objective Finding the right time for offering specialized palliative care to patients with incurable cancer remains challenging. The aim of the scoping review was to identify appropriate entity-specific criteria. Method A scoping review was conducted in the online databases PubMed and Scopus in February 2020. The aim of the literature search was to identify original English- and German-language papers published between 2009 and February 2020 providing evidence on which entity-specific and entity-independent criteria of non- curable cancers are used to integrate affected patients into specialized palliative care in a timely manner. A total of 13 relevant articles were identified. In accordance with the method of the scoping review, a formal assessment of the methodological quality of the included literature was not performed. Results The relevant publications included six reviews and seven original articles. None of the publications analysed explicitly cited characteristic criteria related to specific cancer entities. Incurability/advanced tumour disease, quality of life, distressing symptoms, ECOG status, psychosocial needs, comorbidities, tumour-associated complications, treatment decision/ no treatment options, and limited lifetime prognosis were used or suggested as criteria for integration into specialized palliative care independently of cancer entity. Tools were used to elicit the criteria. No specific characteristic scores were specified for the tools that could detect an expression of the criteria relevant for integration into specialized palliative care. Conclusion To determine the moment of timely integration of specialized palliative care for non-curable cancers, there are no entity-specific criteria and parameters to date. However, it can be deduced from the analysis that all patients with a non-curable or advanced cancer suffering from a reduction/loss of their quality of life and a complex symptom burden, especially depression and pain, should receive the offer of specialized palliative care, irrespective of their entity. Defining criteria in general as characteristic values and consecutively defining a measured value or cutoff value could be a possibility to facilitate a timely integration of palliative care via e. g., a scoring system. So far, it is unclear which combinations of survey instruments or screening tools could serve to capture timely integration.
CRIS-Team WoS Importer:2023-05-05

Evaluating the implementation of national recommendations on multidrug-resistant bacterial microorganisms in end-of-life care - Heckel, Maria; Illig, Annabell; Brunner, Sarah; Ostgathe, Christoph (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2020)
Introduction: In 2017, a national recommendation on multidrug-resistant bacterial microorganisms (MDRO) in end-of-life care was published. In order to monitor the implementation in a hospital-based palliative care unit, a dedicated multidisciplinary working group on MDRO was established. It developed a standard operating procedure and a documentation template (checklist). The aim of the present study is to evaluate the implementation status after one year. Methods: A mixed-methods approach was selected. The status of implementation was identified through a survey among staff members. A retrospective routine data analysis was performed. A focus group discussion with members of the working group focused on previous steps, factors conducive to implementation and on remaining problems. Results: Almost all (18 out of 20) participants (20 out of 29 eligible staff members) knew the national recommendations. Twelve out of 27 recommendations had a high degree of implementation after one year, another 13 recommendations were seen as at least partly integrated into daily routine. For two recommendations the degree of implementation was rated low: (i) ”Taking into account any additional time constraint imposed by protection and isolation measures when planning for personnel and bed occupancy”, and (ii) ”Facilitating the patient's ability to distinguish and recognize team members and family caregivers”. Working group members reported improvements since the implementation, whilst reporting some uncertainty prevailing among both staff members and visitors. Inhibitory factors were said to include the complexity of the standard operating procedure, inadequate usage and poor usability of the checklist. Behavioural and cognitive barriers such as anxieties related to transmission and the sense of security caused by the routine use of protective clothing were considered to be strong. Improving the checklist and the standard operating procedure as well as anchoring procedures in daily routine were considered to be the next important steps. Discussion: The implementation of recommendations is an iterative process and requires the ongoing development of appropriate measures for implementation in the respective institution. A multidisciplinary working group with monitoring tasks is an advantage.
CRIS-Team Scopus Importer:2020-11-20
Keywords: End-of-life care; Evaluation research; Infection control; Palliative care; Patient safety

Health- and disease-related data of inpatients in palliative care units of the Comprehensive Cancer Centers and other hospitals in comparison-Data from the Hospice and Palliative Care Register - Brunner, Sarah; Heckel, Maria; Zenz, Daniel; Ostgathe, Christoph; Gahr, Susanne (Wiener Medizinische Wochenschrift, 2022)
Background The National Hospice and Palliative Registry is a database for palliative care facilities documenting a core data set for quality assurance and scientific evaluations. Objectives The study aims identifying differences between patients in palliative care units treated in Comprehensive Cancer Centers (CCC) or other hospitals (OH) focussing on sociodemographic and health/disease-related characteristics. Methods Descriptive data analysis using IBM SPSS Statistics 21 included patients treated from 2014 to 2018. Comparisons included sociodemographic data, diagnoses, ECOG status and treatment duration. Results 12,922 patient data were analyzed (CCC n = 4975/OH = 7947). In CCCs 79.8% had a tumor diagnosis, in other hospitals 85.1%. The proportion of patients with ECOG 4 was higher in CCCs than in other hospitals. The average length of stay in CCCs was 12.6 days, in other hospitals 11.3 days (p = 0.023). Conclusions Data show differences between patients in palliative care implicating CCCs treating more complex palliative care patients than other hospitals.
CRIS-Team WoS Importer:2022-02-11

Implementation of Best Practice Recommendations for Palliative Care in German Comprehensive Cancer Centers - Gahr, Susanne; Lödel, Sarah; Berenot, Julia; Thomas, Michael; Ostgathe, Christoph (Oncologist, 2019)
Background From 2014 to 2017, the Palliative Medicine Working Group developed and published best practice recommendations for the integration of palliative care in Comprehensive Cancer Centers (CCCs) in Germany. To evaluate the implementation level of these recommendations in the CCCs an online survey was performed. Based on the results of this study, strategic tandem partnerships between CCCs should be built in order to foster further local development. Materials and Methods Directors of all CCCs were contacted by e-mail between December 2017 and February 2018. At the time of the survey, 15 CCCs were funded by the German Cancer Aid. The level of implementation of the recommendations in individual CCCs was established using a transtheoretical model. Results Between December 2017 and February 2018, all 15 contacted directors or their representatives of the CCCs took part in the survey. More than two thirds of the CCCs have a palliative service as well as a day clinic and palliative outpatient clinic. Regional networking and the provision of a palliative care unit were approved by all CCCs. Conclusion The publication of best practice recommendations was a milestone for the integration of palliative care in the CCCs. The majority of the German CCCs already fulfill essential organizational and structural requirements. There is a particular need for optimization in the provision of a basic qualification for general palliative care and emergency admission personnel. Implications for Practice In 2017, the Palliative Medicine Working Group in the network of the German Comprehensive Cancer Centers (CCCs) published the best practice recommendations it had developed for the integration of palliative medicine in CCCs in Germany. In order to evaluate the level of implementation of the recommendations, an online survey of the CCC directors was established. The majority of German CCCs fulfil elementary organizational and structural requirements. However, there is still room for improvement in the provision of a basic qualification for general palliative care and emergency admission personnel.
CRIS-Team WoS Importer:2019-09-27

Palliative Care Teams in the German Comprehensive Cancer Centers - Gahr, Susanne; Berendt, Julia; Lödel, Sarah; Ostgathe, Christoph; Simon, Steffen T.; Tewes, Mitra; Zader, Kirsten; Schwartz, Jacqueline; Neukirchen, Martin (Deutsche Medizinische Wochenschrift, 2019)
BACKGROUND: A palliative care team is recognized as a quality indicator in the consultation and care of patients with a tumor disease and is used nationally (92 %) in the National Cancer Institutes, model of the German Comprehensive Cancer Center (CCC). This begs the question of how palliative care teams are presently integrated into the CCCs. METHOD: From July to August 2017, a paper-based quantitative survey of 16 locations of the CCCs, supported to that date, gathered information on the existence, personnel situation, use and prospects of a specialized inpatient palliative care service. The survey was addressed to the heads of the palliative medical units of the CCCs. The data were evaluated in SPSS (frequency, median, mean, range). RESULTS: Fifteen CCCs took part in the survey (response 94 %). Thirteen of the fifteen CCCs have a service that also treats palliative patients. Twelve of thirteen CCCs of these are attainable during regular working hours (8a. m.-4 p. m. on weekdays). All services are staffed by physicians, additional eleven are staffed by nurses. Seven services are besides physicians and nurses joined by other professions. In 2016, 4482 median co-treatments were provided by the services, 80 % of these as additional charges without revenue and without codable OPS. In 2017, five centers plan to charge ZE 2017-133, two centers ZE 60 and three centers both intend to charge ZE 2017-133. CONCLUSIONS: Services for palliative patients exist generally in the German CCCs, but only half of them satisfy the condition of multi-professionality required for the fulfillment of the german guidelines. The new surcharge introduced in 2017, which can be charged on an hourly basis, could create improvements in this regard and contribute to cost recovery. Thus, contrary to the previous arrangement, essential and reasonable performances with a time of treatment of less than seven days can be charged.
EVALuna2:204833

Quick start file for the panel "Labour market and social security" (PASS) - Fuchs, Benjamin; Lödel, Sarah; Otto, Michael (2015)

SOP - Management of multiresistent Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Heckel, Maria; Brunner, Sarah; Gahr, Susanne; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Foertsch, Baerbel; Klein, Carsten (Die Onkologie, 2022)
Infobox 1 SOP aus der Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der AG Palliativmedizin der von der Deutschen Krebshilfe geförderten Comprehensive Cancer Center (CCC
CRIS-Team WoS Importer:2022-10-07

Standard Operating Procedures (SOPs) for Palliative Care in German Comprehensive Cancer Centers - An evaluation of the implementation status - Lödel, Sarah; Ostgathe, Christoph; Heckel, Maria; Oechsle, Karin; Gahr, Susanne (BMC Palliative Care, 2020)
Background: The working group for palliative medicine within the Comprehensive Cancer Center (CCC) network funded by the German Cancer Aid in Germany has developed and published 14 Standard Operating Procedures (SOPs) for palliative care in CCCs. This study analyzed to what extent these SOPs have been implemented in the clinical routine in the CCC network one year after their publication. Methods: An online-based survey on the implementation status, limitations in daily practice and further themes was conducted between April and July 2018. In total, 125 health professionals in specialized palliative care from all 16 CCC locations were invited to participate. The data were analyzed descriptively using SPSS. Results: The response rate was 52.8%. More than half of the respondents (57.6%) knew about the free availability of SOPs on the CCC network website. The extent to which each SOP was being used actively in practice by the survey respondents ranged from a low of 22.7% (for the "Fatigue" SOP) to a highest of 48.5% (for the "Palliative Sedation" and "Respiratory Distress" SOPs). The respondents became aware of the SOP through recommendations from colleagues, team meetings or from the head of the department. The SOPs "Respiratory distress of an adult palliative patient" and "Palliative sedation" were perceived as the most practically oriented and understandable. Barriers to use SOPs were mainly limited time resources and lack of knowledge of existence and availability. Conclusions: In practice, better knowledge about the SOPs and at the same time increased use can be achieved through systematic training or discussion of SOPs in regular team meetings. There is a need to take measures to optimize the implementation in clinical practice.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Comprehensive Cancer Center (CCC); Implementation status; Palliative Care; Standard Operating Procedure (SOP); Survey; Symptoms

Symptom burden and relief in palliative care units of German Comprehensive Cancer Center and other hospitals - Berendt, Julia; Brunner, Sarah; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph; Gahr, Susanne (Journal of Cancer Research and Clinical Oncology, 2024)
Purpose: The National Hospice and Palliative Registry contains patient data from German hospice and palliative care facilities about symptoms. The aim of the study at hand is to differentiate symptom burden of patients in palliative care units between Comprehensive Cancer Center (CCC) and other hospitals regarding symptom burden and relief of patients in palliative care units. Methods: The registry analysis provided data of patients in palliative care units (2014–2018). We analyzed characteristic and symptom-related data on 18 symptoms, with considerable symptom-burdened patients (moderate or severe). We followed a cancer (yes/no) and facility-specific descriptive analysis (f, %, μ, Mdn, SD, V, r) using SPSS. Results: We evaluated 10,447 patient records (CCC: 4234 pts/non CCC 6,213 pts), 82% with a cancer diagnosis. For cancer patients, the mean age in CCC-affiliated palliative care units was 68 (SD 19–99) years, in others 73 (SD 23–104) years (p < 0.05; V = 0.2). The proportion of patients with significant symptom burden is lower in CCC-affiliated than in other palliative care units. The difference between facilities shows a significant weak effect in pain, vomiting and constipation, depressiveness, anxiety, and tension. The proportion of cases which symptom burden could be alleviated is higher in CCC-affiliated palliative care units with significant weak/medium effect in pain, nausea, vomiting, shortness of breath, constipation, wound care problems, depressiveness, anxiety, tension, confusion, and problems in organizing care. Conclusion: We found differences in symptom burden and symptom relief between CCC-affiliated and other palliative care units. CCCs should continue to feel responsible for sharing knowledge about symptom relief, such as through standard operating procedures and education.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Cancer; Palliative care; Registry; Symptom burden; Symptom relief